Socio-demographic indicators of alcohol dependence in patients treated for addiction in a post-industrial city - Marcin Kozak; Magdalena Piegza; Piotr Ścisło; Karina Badura-Brzoza; Piotr Wacław Gorczyca (Medycyna Pracy, 2019)
Background The aim of the study was to evaluate the influence of the place of living on the prevalence of the alcohol dependence syndrome (ADS) and to find its possible connections with socio-demographic data within a post-industrial city with a population > 100 000 inhabitants.